Droplet-based cytotoxicity assay: implementation of time-efficient screening of antitumor activity of natural killer cells - Antona, Silvia; Platzman, Ilia; Spatz, Joachim P. (ACS omega, 2020)
Natural killer (NK) cells are key players of the innate immune system. Due to their rapid cytotoxicity against infectious pathogens, hematologic malignancies, and solid tumors, NK cells represent solid candidates for cell-based immunotherapy. Despite the progress made in recent years, the heterogeneity in their cytotoxic behavior represents a drawback. With the goal of screening the intrinsic diversity of NK cells, droplet-based microfluidic technology is exploited to develop a single-cell time-efficient cytotoxicity assay. Toward this end, NK-92 cells are coencapsulated with hematological tumor cell lines in water-in-oil droplets of different sizes and their cytotoxic activity is evaluated. The effect of droplet-based confinement on NK cytotoxicity is investigated by controlling the droplet volume. The successful optimization of the droplet size allows for time efficiency compared to cytotoxicity assays based on flow cytometry. Additionally, the ability of individual NK-92 cells to kill multiple target cells in series is explored, expanding the knowledge about the serial killing process dynamics. The developed droplet-based microfluidic assay does not require the labeling of NK cells and represents a step toward developing of a forthcoming process for the selection of NK cells with the highest cytotoxicity against specific targets.
Gesehen am 05.11.2020